2018
DOI: 10.1021/acs.energyfuels.7b03839
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Enhanced Oil Recovery of Extra Heavy Oil by Supercritical Water Flooding

Abstract: Exploitation of deep extra heavy oil is a challenging work due to its high viscosity and high reservoir pressure. Supercritical water is first proposed as an injection agent, considering its favorable physiochemical properties. A novel flooding experimental system with a design temperature up to 450 °C and pressure up to 30 MPa was developed to demonstrate the feasibility of supercritical water flooding (SCWF) technology. A sand pack core with an adiabatic boundary was used to eliminate heat unbalance. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…The sub/supercritical water with a higher diffusion coefficient and lower viscosity had driving and swelling effects during pyrolysis of oil shale. 37 These effects could make the phase interface disappear and reduce the interfacial tension, thereby reducing the viscosity and improving the fluidity of the oil. Also, the generated oil was dissolved in sub/supercritical water to form a miscible phase due to their strong solubility and easily migrated to the outside.…”
Section: Resultsmentioning
confidence: 99%
“…The sub/supercritical water with a higher diffusion coefficient and lower viscosity had driving and swelling effects during pyrolysis of oil shale. 37 These effects could make the phase interface disappear and reduce the interfacial tension, thereby reducing the viscosity and improving the fluidity of the oil. Also, the generated oil was dissolved in sub/supercritical water to form a miscible phase due to their strong solubility and easily migrated to the outside.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there is a constant increase in the depth of oil mining wells, and the exploration environment is becoming increasingly complex [ 1 ]. To make accessing deep deposits easier, scholars have proposed traditional water flooding technology, fine water injection technology, supercritical water flooding technology, and other water drive technologies [ 2 , 3 ]. Water flooding technology was previously developed, and this research is relatively mature.…”
Section: Introductionmentioning
confidence: 99%
“…As a special thermodynamic state of water (temperature > 374°C and pressure > 22:1 MPa), SCW can behave as an organic solvent with a good solubility of hydrocarbon [9,10] and substantially increase oil mobility by upgrading [11][12][13]. Inspired by this favourable feature, Zhao et al studied the viability of SCW flooding on heavy oil recovery by experiments and confirmed that SCW flooding is capable of enhancing heavy oil recovery [14]. They also proposed that the main EOR mechanisms of SCW flooding were miscible flooding, heavy oil upgrading, and override suppression [15,16].…”
Section: Introductionmentioning
confidence: 99%